Senescent Cell Depletion Through Targeting BCL-Family Proteins and Mitochondria - Fan, Ying; Cheng, Jiaoqi; Zeng, Huihong; Shao, Lijian (Frontiers in Physiology, 2020)
Senescent cells with replicative arrest can be generated during genotoxic, oxidative and oncogenic stress. Long-term retention of senescent cells in the body, which is attributed to highly expressed BCL-family proteins, chronically damages tissues mainly through senescence-associated secretory phenotype. It has been documented that accumulation of senescent cells contributes to chronic diseases and aging-related diseases. Despite the fact that no unique marker is available to identify senescent cells, increased p16INK4a expression has long been used as an in vitro and in vivo marker of senescent cells. We reviewed existing five p16INK4a reporter mouse models to detect, isolate and deplete senescent cells. Senescent cells express high levels of anti-apoptotic and pro-apoptotic genes compared to normal cells. Thus, disrupting the balance between anti-apoptotic and pro-apoptotic gene expression, such as ABT-263 and ABT-737, can activate the apoptotic signaling pathway and remove senescent cells. Mitochondrial abnormalities in senescent cells were also discussed, for example mitochondrial DNA mutation accumulation, dysfunctional mitophagy and mitochondrial unfolded protein response. The mitochondrial-targeted tamoxifen MitoTam can efficiently remove senescent cells due to its inhibition of respiratory complex I and low expression of adenine nucleotide translocase-2 in senescent cells. Therefore, senescent cells can be removed by various strategies, which delays chronic and aging-related diseases and enhances lifespan and healthy condition in the body.